Anti-Counterfeit Technology of Halftone Image Watermarking by Digital Screening - Qifeng Chen; Guangxue Chen; Shuangshuang Wen; Jinglei Tai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
From the point of view of the digital printing, this paper focused on researching the anti-counterfeit print technology of halftone images and directly detecting techniques combined with digital image processing technology, thereby enhancing the security features of the printed mater. The grating has converged effect on light in the corresponding direction, which makes it compress and isolate images. According to this feature of grating, the variable angle algorithm of screening anti-counterfeit technology was proposed, and in accordance with the algorithm, the experiment of grating extracting the watermarking of halftone image was studied in this paper. In this experiment, we designed other screening angles to hide the information, we called it the variable angle screening security technology. When detecting the hidden information, only at the same angle could we observe the security effect with corresponding lines of the grating. The experimental results showed that the variable angle algorithm of screening anti-counterfeit technology had nice security effect, and could be used in practical application. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3252